Chemical engineering fluid mechanics - Darby, Ron (Marcel Dekker, 2001)
Basic concepts - Dimensional analysis and scale-un - Fluid propierties in perspective - Fluid statics - Conservation principles - Pipe flow - Internal flow applications - Pumps and compressors - Compressible flows - Flow measurement and control - External flows - Fliud-solid separatinos by free settling - Flow in porous media - Fluidization and sedimentation. - Two-phase flow.